(untitled) (Blockchain Technology and Distributed Systems, 2023)
Blockchain technology has garnered significant attention for its potential to revolutionize various industries. However, one of the primary challenges facing blockchain adoption is scalability. As the number of transactions on blockchain networks increases, the scalability of these networks becomes a critical issue. Layer 2 protocols and sharding are two key scalability solutions that aim to address this challenge. Layer 2 protocols, such as the Lightning Network, enable off-chain transactions, reducing the burden on the main blockchain. Sharding, on the other hand, partitions the blockchain into smaller shards, allowing for parallel transaction processing. This paper provides a comprehensive analysis of layer 2 protocols and sharding techniques, discussing their advantages, limitations, and potential impact on blockchain scalability. By examining these scalability solutions, this paper aims to provide insights into how blockchain networks can achieve higher transaction throughput without compromising decentralization and security.